Buku Sejarah Desa Blondo : Menggali Sejarah, Keindahan Alam, Serta Kearifan Lokal yang Tersimpan di Desa Blondo, Kecamatan Mungkid, Kabupaten Magelang - Desy Kristiyati; Novia Ramadhani; Salwa Muthia Azzahra Alam; Nadilla Anissa Fatin; Raken Arya Seta; Laila Itsna Nurbaiti; Rizkya Sukma Putri; Nadya Ferizka Graha; Antariksa Dara Nirmala; Hasyim Effendi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This community service through the Community Service Program (KKN) aims to document the history, culture, and tourism potential of Blondo Village, Mungkid District, Magelang Regency, in the form of a book entitled The Story of Blondo. Blondo Village has diverse tourism potential, including natural, religious, and culinary tourism that can be developed to improve the welfare of the community. This program uses descriptive qualitative methods with data collection techniques through field observations, interviews with community leaders, and documentation from various sources. The resulting book consists of 52 pages that discuss the origin of the village, socio-cultural development, and tourism recommendations. The results of this program show that The Story of Blondo book can be an educational medium for the community, especially the younger generation, to better understand the history and culture of their village. In addition, this book acts as an effective tourism promotion tool for local and foreign visitors. The main advantage of this book lies in the concise, systematic presentation of information, and is complemented by documentary images to strengthen the historical narrative. However, the limited coverage of the historical period covered is one of the weaknesses that could be improved through further editions or periodic updates.